War and conflict and their relationship with exchange rate volatility, governance and biodiversity - Yiew, Thian Hee (2016)
Armed conflict causes death and sufferings to the civilian population. Besides the loss of human lives and suffering of civilian population, armed conflicts have severeeffects on social, economic and national politics. In the new global economy, the determinants of armed conflict have become important issues that are attracting the attention and focus of researchers. The purpose of this study is to investigate the relationship between armed conflicts and select economic factors such as exchange rate volatility, governance and biodiversity. Exchange rate volatility creates exchange rate risk that will affect international trade and may cause capital flight.This situation will lead to a slowdown of economic growth, increase economic hardship and poverty that will increase the risk of an armed conflict. However, the impact of exchange rate volatility on armed conflict is still vague. Using data from 74 developing countries with internal armed conflict from 1970 until 2012, this study applies logit, probit, pooled ordinary least square (POLS), negative binomial (NB),and hurdle models to estimate the impact of exchange rate volatility on armed conflict. The results suggest that higher exchange rate volatility increases the risk of armed conflict. This study also finds that slow economic growth, increase population,increase terrain ruggedness will increase the risk of armed conflict. In addition, the relationship between primary commodity export volatility with armed conflict is inverted U-shape. On the other and,economists recognized that a country run with poor governance would encourage corruption and injustice that could develop widespread overty.Consequently, citizens will come to bear with high grievances and the desire for redress, factors that could trigger armed confrontation with the incompetent government. To determine the impact of governance on armed conflict,this study employed data from 80 developing countries for the period 1996 – 2013 and applied logit, probit, POLS, NB, and hurdle models. The results of the study indicate that governance indicators such as voice and accountability, political stability and absence of violence, government effectiveness, regulatory quality, rule of law and control of corruption are negatively correlated with armed conflict. In other words, poor governance increases the risk of armed conflict. Lastly, this study investigates the impact of armed conflicts on biodiversity. Armies hunting for food as well as extract forest produce from the forest in the combat zone could result in severe forest destruction, and enormous loss in biodiversity. In this study, the number of threatened species – plant, mammal, fish and bird species; was used to proxy for biodiversity loss. The results indicate that increase in armed conflict will have negative impact on the number of threatened plant and fish species as well as on biodiversity loss. In conclusion, the results of this study indicate that countries with good policy and good governance will reduce the onset of armed conflict and consequently will be able to mitigate biodiversity loss.